CORRELATION BETWEEN MOTHERS KNOWLEDGE ABOUT THE LUNG TUBERCULOSIS IN EFFORTS TO PREVENTED THE LUNG TUBERCULOSIS AT CHILD 0-5 YEARS OLD IN THE POSYANDU NUSA INDAH DESA JABUNG KEC. GANTIWARNO KAB. KLATEN - KLATEN, STIKES DUTAGAMA (STIKES DUTAGAMA KLATEN, 2012)
Background: Tuberculosis still constitude the first cause of illness and death in the developing country. The number Tuberculosis of child more less 5-15% from amount sufferer of Tuberculosis. It is about 15 million the new sufferer and 5 million will be happened between child on 5 years old of death (DepKes RI 2003). Objectives: To know the relationship between mother?s knowledge about the lung Tuberculosis in efforts to prevention the lung tuberculosis at child 0-5 years old in the ?Posyandu Nusa Indah Desa Jabung Kecamatan Gantiwarno Kabupaten Klaten?. The Method of Research: The kind of research which used is analytical correlation with survey cross sectional approach that is to knows the mother?s knowlwdge about the lung Tuberculosis in the efforts to prevention the lung tuberculosis at child 0-5 years old in the ?Posyandu Nusa Indah Desa Jabung Kecamatan Gantiwarno Kabupaten Klaten?. The sample which used as many as 70 of mother with interpretation cluster sampling technique. The correlation analysis which used is spearman Rank (Rho). Result: the result of research obtain the significan relation between mother?s knowledge about lung tuberculosis in the efforts to prevention the lung Tuberculosis to child 0-5 years old at ?Posyandu Nusa Indah Desa Jabung Kecamatan Gantiwarno Kabupaten Klaten? with t count 4, 157 and t table 2,000 p Value 0,000 (p<0,05). Conclution: It be found the significant relationship between both of variable that are knowledge in the efforts to prevention.